ANALISIS KOMPARASI PREDIKSI FINANCIAL DISTRESS METODE GROVER, ALTMAN, SPRINGATE, ZMIJEWSKI, DAN OHLSON PADA PERUSAHAAN PERTAMBANGAN DI BEI - Komarudin Komarudin; Syafnita Syafnita; Amalia Ilmiani (Fakultas Ekonomi Universitas Pekalongan, 2019)
This study aims to determine whether there are differences between the Grover, Altman, Springate, Zmijewski, and Ohlson models to predict financial distress. And to find out which financial distress prediction models are best applied to mining companies in Indonesia. Comparison of the five models is done by analyzing the accuracy of each model, using the real conditions of the company. The population in this study amounted to 39 mining companies listed on the Stock Exchange, the sampling technique in this study was purposive sampling. From the results of the sample calculation, it is known that companies that meet the requirements to be used as samples of the company are 13 companies. The analytical tool used in this study is Two Way ANOVA. Based on data analysis it is known that there are differences between the five bankruptcy analysis models used in this study except the Altman and Ohlson models in the test results are not significant, which is equal to 0.105. And the accuracy of the Grover model is 64.10%, the Altman model is 66.67%, Springate is 48.72%, Zmijewski is 61.54%, and Ohlson is 25.64%. Among the five bankruptcy analysis models that have the highest level of accuracy are the Altman model. Keywords: Financial Distress and Bankruptcy Prediction Method.